First principles study of toxic gas molecules adsorption on Group IVA (C, Si, Ge) 2-Dimensional Materials - Zainal, Mohd Azizul; Chan, Kar Tim; Zainuddin, Hishamuddin; Mohd Shah, Nurisya; Raymond Ooi, Chong Heng (Penerbit Universiti Kebangsaan Malaysia (UKM Press), 2023)
Two-dimensional materials from group IVA namely graphene, silicene, and germanene have gained research interest in various fields of applications recently due to their extraordinary properties. These substrates have been successfully synthesized and are found to have interesting gas sensing capabilities. In this work, first-principles study using density functional theory is carried out to investigate the adsorption of toxic gases such as CO, Cl2, NO2, and COCl2 on these monolayers. We analyze the best adsorption site and orientation for these molecules on the monolayers by calculating the adsorption energy. Charge transfer, the density of state (DOS) and band diagram calculations are performed to explore the changes in their electronic and structural properties due to the adsorbed gas molecules. As for the sensing performance, crude estimations of the sensitivity and recovery time are performed. The results show that silicene and germanene monolayers are better at detecting CO and NO2 as compared to graphene. They have a short recovery time for CO but a long recovery time for NO2 implying that they are better for scavenging NO2. Besides, silicene is also a better gas sensor for chlorine gas with a 44 min recovery time. As for graphene, it is the best gas sensor for phosgene among the substrates. This study gives a clear prediction of substrates for the detection of these toxic gases.